Comparative study on evaporator heat transfer characteristics of revolving heat pipes filled with R134a, R22 and R410A - Yau, Yat Huang; Foo, Y.C. (Elsevier, 2011)
Heat pipes are used extensively in various applications including the heating, ventilating and air conditioning (HVAC) systems. The high thermal conductivity of the device, attributed from the two-phase heat transfer processes within the heat pipe, made them superior heat exchanger devices. Heat pipes had been widely used in HVAC applications in energy conservation, dehumidification enhancement, heat dissipation, etc. A number of researches have been conducted to expand the applicability of heat pipes in HVAC in Malaysia, especially in air-to-air heat recovery using stationary heat pipes. However, the potential usage of rotating heat pipe in heat recovery in tropical countries like Malaysia was yet to be explored. Hence, the potential of rotating heat pipe in the HVAC systems used in tropics was explored through a parametric study that incorporates rotational speeds, off-axis displacements and varied refrigerants. The rotating heat pipes charged with R134a, R22 and R410A were tested with varied radial displacement from the rotational axis. The straight and leveled heat pipe with the furthest radial displacement yields the most significant heat transfer, which was attributed to the magnitude of the generated centrifugal force, and effective distribution of liquid in the evaporator. © 2010 Elsevier Ltd.